Understanding social system drivers of green building innovation adoption in emerging market countries: The role of foreign direct investment. (September 2019) - Devine, Avis; McCollum, Meagan
Abstract: There has been a growing academic focus on the economic, environmental, and social implications of sustainable innovation adoption. This work has largely focused on the developed world, yet the majority of people and future economic growth lies in the developing world. Further, most research examines micro data on consumers or firms, limiting what is known regarding the role of macro factors on diffusion, such as social systems. Addressing these limitations, this research provides the first high-level insights into how green building adoption is occurring in developing countries. Utilizing a hand-collected dataset of all green building certification activity in 97 emerging market countries over fifteen years, we examine the relationship between economic development and green building adoption. We find the use of international certification programs is far more common than domestic programs, and that domestic programs have only been originated in advanced emerging economies. Additionally, we observe a relationship between foreign direct investment into emerging markets countries and the proliferation of green building, and that in most cases, domestic certification programs only originate after international certification activity has been introduced to the local economy. Our findings carry economic and policy implications, worthy of consideration by both those interested in offering and attracting foreign investment in emerging market countries. Highlights: Studies the impact of social systems on innovation adoption Analyzes green building adoption and diffusion in 97 developing countries FDI diffuses green building certification to developing countries. International certification adoption precedes domestic certification program creation.